Komunikasi Interprofesional Dalam Peningkatan Keselamatan Pasien: Systematic Review - Hirza Ainin Nur; Agus Santoso (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2018)
Background: Interprofessional communication is an important element in providing health services to patients. Failure in communication between health workers can lead to adverse events that occur in hospitals. Research Objectives: To determine the effectiveness of interprofessional communication to improve patient safety. Method & Source of data: The method used was a systematic review. Data sources obtained from the journal Ebsco, PubMed, and Google Scholar. Inclusion & exclusion criteria: Journal related to the form of interprofessional communication development, English-language journals, year of publication between 2011-2016, journal full-text pdf. Results: from four journal articles reviewed, the results show that interprofessional communication is effective to improve patient safety at the hospital. Conclusion: Interprofessional communication is effective to improve patient safety and reduce the incidence of patient safety at the hospital.